2008
DOI: 10.1539/joh.l7097
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Head Wash Cooling Protocol Using Non‐Refrigerated Water in Reducing Heat Stress

Abstract: Health, Japan-Envisioning a cooling method and aiming at maximum feasibility and simplicity, we designed an experimental intervention-control study based on non-refrigerated water usage, consisting of pouring 2 l of 23.0°C water simultaneously on head and hands for one minute, after every 20 min of exertion. The subjects were 11 fit male individuals between 19 and 26 yr old. Each individual participated in one control and one intervention measurement in a climatic chamber at 35°C and 60% humidity (31.5°C WBGT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The observed competitiveness that developed between firefighters may also contribute to improved test performance. One study showed improved processing speed in the Headminders Cognitive Stability Index (CSI) test in participants who were 3.27% dehydrated on average 50. The improved processing speed found in that study may be similar to the reduced interference score (increased number of conflicting colors stated) of the firefighters in the current study; however, the firefighters in the current study were dehydrated to a lesser degree, demonstrating less than one percent dehydration on average.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…The observed competitiveness that developed between firefighters may also contribute to improved test performance. One study showed improved processing speed in the Headminders Cognitive Stability Index (CSI) test in participants who were 3.27% dehydrated on average 50. The improved processing speed found in that study may be similar to the reduced interference score (increased number of conflicting colors stated) of the firefighters in the current study; however, the firefighters in the current study were dehydrated to a lesser degree, demonstrating less than one percent dehydration on average.…”
supporting
confidence: 61%
“…This had no significant effect on reducing rectal temperature or HR. 50 However, head wash cooling did significantly improve the partcipants' perception of alertness, concentration capacity, equilibrium, and tiredness. 50 Simmons et al investigated the effect of head and neck cooling on high core temperature.…”
Section: Cooling During Activitymentioning
confidence: 90%
See 2 more Smart Citations
“…Some authors describe heat exhaustion as an early stage of, or a warning for impending heat stroke [2;8]. Other authors put both heat exhaustion and heat stroke at the same category [9], or suggest some overlap between the two disorders. Heat exhaustion is mostly ill-defined in literature, with absent diagnostic criteria, and inconsistent recommendations of management [10].…”
Section: Introductionmentioning
confidence: 99%